Analysis of site of perforation during access preparation - a retrospective study - PRIADARSINI T; SOWMYA K; GANAPATHY, DHANRAJ (The journal of contemporary issues in business and government, 2020)
Perforation results in communication between the root canal walls and the periodontal space. It is commonly caused by operative procedural accidents or due to extensive caries, external and internal inflammatory root resorption . Perforations during a root canal treatment may increase the risk of failure for the involved tooth. The prognosis of a perforated tooth depends on factors like location and the size of the perforation, potential microbial colonization of the endodontic system, the time lapse between the occurrence of the perforation and repair, and the type of filling material used. For the long-term success of the root canal system, it is essential to emphasize disinfection and sterilization at the perforation site and the remaining root canal system. Nonsurgical management is possible with predictable prognosis if the right treatment is planned and executed.The aim of this study was to find the association of age, gender and tooth arch with the site of perforation during access cavity preparation. The data was collected from patients visiting Saveetha dental College for treatment. Totally 41 perforations were identified and treated completely. The data was entered in excel sheet and exported to IBM SPSS software version 20.0 and statistical analysis done. The number of perforations were higher in females and in the age group above 40 years, however no significant association was found for site of perforation with age and gender. Number of coronal perforations were more than furcal perforation and this association between tooth arch and site of perforation was found to be statistically significant (P value- 0.006 < 0.05; Chi square test). Proper knowledge of anatomy and principles of access cavity is essential to prevent these iatrogenic errors.